Integration of Technology and Future Curriculum Design to Enhance the Efficiency and Relevance of Digital Learning - Madha Komala; Syabba Usaima Yamtaz; Teresia Antini Senda (Green Publisher, 2025)
The purpose of this article is to analyze strategies for integrating technology into future curriculum design to enhance the efficiency, flexibility, and relevance of digital learning. This study employs a literature review method by examining ten national and international journals published within the last five years, focusing on the roles of artificial intelligence (AI), big data, and adaptive learning models such as flipped classroom and hybrid learning. The findings indicate that systematically designed technology integration can create learning experiences that are personalized, interactive, and data-driven, while also supporting the achievement of 21st-century competencies. However, challenges such as limited infrastructure, teacher readiness, and ethical issues related to data usage remain significant obstacles. Therefore, technology integration in curriculum development should be implemented inclusively, sustainably, and responsively, taking into account both local contexts and global educational dynamics.